Pursuing an Always-on Connected Network Architecture through INTERA - Carvalho, Leandro; Passito, Alexandre; Jorge, Saulo; Péricles, Laércio; Mota, Edjard (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2008)
It is expected for the next years that any nontrivial device will contain some degree of embedded processing and communications capability. In this new environment, the focus shifts from individual devices to an “environmental user interface,” acting as a contextual user access and information delivery engine across multiple interconnected devices. As an intermediate step to reach this goal, we present the Intelligent Routing Architecture (INTERA), whose core is a logical router responsible for checking network status and determining the best route(s) for packet forwarding. From INTERA concept, we present some challenges to be tackled in order to achieve fully dependable, scalable, and ubiquitous computer systems.